Analysis Social Media As An Employee Recruitment Tool At Pt Atl - Firda Amelia; Christian Wiradendi Wolor; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research aims to explain the implementation of online recruitment via social media as an employee recruitment tool at PT ATL Current recruitment methods encourage companies to follow changes by using social media to support activities carried out by companies such as disseminating information related to job vacancies and interacting with applicants. By comparing several social media, this research attempts to identify the advantages and disadvantages of each social media. The method used in this research is a qualitative descriptive method and the data sources used are primary and secondary data obtained using a semi-structured interview method with Human Resources and employees involved in the recruitment process. Data collection was carried out through observation, interviews and documentation studies. The results of the research show that respondents responded to questions asked by researchers regarding the recruitment system that PT ATL had implemented a recruitment system appropriately and optimally but needed a little improvement in the recruitment and selection system.